Evaluation of the efficiency of microwave heating of soils - Bondarenko, Oksana; Boshkova, Irуna (Technology audit and production reserves (Online), 2023)
One of the innovative directions of heat treatment of soil in the technologies of decontamination from pesticides, oil products and disinfection is heating in a microwave electromagnetic field. Numerical studies testify to the effectiveness of the microwave treatment method. This is due to the peculiarities of the interaction of the microwave field with dielectric materials. Unique effects arise, such as the possibility of local heating, volume heating of the material, unidirectionality of pressure and humidity gradients. This contributes to the intensification of transfer processes and the possibility of energy savings. However, the challenge at present is to determine the processing regimes, including load mass, specific microwave field power, electric field strength, material layer thickness, and processing time, under which the microwave method will be energy efficient. Conducting multifactorial experimental studies allows determining the conditions of energy feasibility of microwave soil treatment. Therefore, the object of research is the process of heating a dense layer of soil under the action of a microwave electromagnetic field. The results of studies on the effect of microwave treatment of soil contaminated with organophosphorus pesticides, contaminated with petroleum products, and under what conditions the qualitative effect was obtained, as well as the results of the effect of the microwave field on the pathogenic microflora of the soil used for growing plants, were considered. The high quality of implementation of soil treatment technologies is determined. Energy efficiency was determined on the basis of data on temperature and moisture content, analysis of thermograms of microwave heating of chernozem and clay soil, analysis of the influence of material layer thickness, influence of dielectric properties and power of the microwave field. According to the results of thermal calculations, the values of the efficiency of the microwave chamber and the intensity of the electric field were determined, which are recommended as the basis for scaling in order to transfer the experimental results to industrial installations. During the research, specific experimental methods of research under microwave heating conditions, analytical methods of thermal calculations, developed by the authors of the experimental research methodology were used. Experimental studies were carried out on the installation created by the authors. The results of the research are intended for the wide implementation into practice of technological calculations of microwave chambers for heat treatment of soils, intensification of disinfection processes under the conditions of energy efficiency of the transformation of the energy of the microwave field into the internal energy of the soil. Одним з інноваційних напрямків термообробки ґрунту в технологіях знезараження від пестицидів, нафтопродуктів та дезінфекції є нагрівання в мікрохвильовому електромагнітному полі. Чисельні дослідження свідчать про ефективність мікрохвильового методу обробки. Це пов’язано з особливостям взаємодії мікрохвильового поля з діелектричними матеріалами. Виникають унікальні ефекти, такі як можливість локального нагрівання, об’ємне нагрівання матеріалу, односпрямованість градієнтів тиску та вологості. Це сприяє інтенсифікації процесів перенесення та можливості енергозаощадження. Проте на даний час проблемою є визначення режимів обробки, які включають масу завантаження, питому потужність мікрохвильового поля, напруженість електричного поля, товщину шару матеріалу та час обробки, за якими мікрохвильовий метод буде енергоефективним. Проведення багатофакторних експериментальних досліджень дозволяють визначити умови енергетичної доцільності мікрохвильової обробки ґрунтів. Отже, об'єктом дослідження є процес нагрівання щільного шару ґрунту при дії мікрохвильового електромагнітного поля. Розглянуто результати досліджень впливу мікрохвильової обробки ґрунтів, забруднених фосфорорганічними пестицидами, забруднених нафтопродуктами, та за якими умовами отриманий якісний ефект, а також результати впливу мікрохвильового поля на патогенну мікрофлору ґрунту, який використовується для вирощування рослин. Визначена висока якість впровадження технологій обробки ґрунту. Енергетична ефективність визначалась на підставі даних за температурою та вологовмістом, аналізу термограм мікрохвильового нагрівання чорноземного та глинистого ґрунту, за аналізом впливу товщини шару матеріалу, впливу діелектричних властивостей та потужності мікрохвильового поля. За результатами теплових розрахунків визначені значення ККД мікрохвильової камери та напруженість електричного поля, що рекомендується як базова для масштабування з метою перенесення експериментальних результатів до установок промислового призначення. Під час проведення досліджень використано специфічні експериментальні методи досліджень в умовах мікрохвильового нагрівання, аналітичні методи проведення теплових розрахунків, розроблені авторами методики обробки експериментальних досліджень. Експериментальні дослідження здійснені на створеній авторами установці. Результати досліджень передбачені для широкого впровадження у практику технологічних розрахунків мікрохвильових камер для термообробки ґрунтів, інтенсифікації процесів знезараження за умовами енергоефективності перетворення енергії мікрохвильового поля у внутрішню енергію ґрунту.